2009
DOI: 10.1007/s11104-009-0066-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of NaCl on growth, water status, N2 fixation, and ion distribution in Pterocarpus officinalis seedlings

Abstract: Pterocarpus officinalis (Fabaceae) dominates in the swamp forests of the Lesser Antilles, submitted to strong variations of soil salinity (30-445 mM). This study aimed to assess the effect of salinity on growth, nodulation, N 2 fixation, water status and ions content in P. officinalis and to clarify the mechanisms involved. Seedlings inoculated or not with two strains from areas of contrasting salinity levels (< to 50 or 445 mM) were watered with 0, 171 and 342 mM solutions of NaCl in greenhouse conditions. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Reductions in growth performance were observed in faba bean under saline conditions (Azooz, 2009). Metwali et al (2015) concluded that salinity caused a significant decrease in all of faba bean growth traits, possibly attributed to inhibited growth and metabolism of legumes, affecting the activity of symbiotic bacteria in roots and limiting nitrogen fixation (Gaballah and Gomaa, 2005;Munns and Tester, 2008;Dulormne et al, 2010). In agreement with our findings, Radi et al (2013) reported that Sakha-1 cultivar succeed in growing and production under salinity conditions.…”
Section: Discussionsupporting
confidence: 90%
“…Reductions in growth performance were observed in faba bean under saline conditions (Azooz, 2009). Metwali et al (2015) concluded that salinity caused a significant decrease in all of faba bean growth traits, possibly attributed to inhibited growth and metabolism of legumes, affecting the activity of symbiotic bacteria in roots and limiting nitrogen fixation (Gaballah and Gomaa, 2005;Munns and Tester, 2008;Dulormne et al, 2010). In agreement with our findings, Radi et al (2013) reported that Sakha-1 cultivar succeed in growing and production under salinity conditions.…”
Section: Discussionsupporting
confidence: 90%
“…As halophyte plants, mangrove trees have adapted to saltwater by means of various physiological mechanisms [27]. Medina et al [28] and Dulormne et al [29] have shown that P. officinalis itself is able to exclude salt not only at the root level but also at leaf level, in the woody rachis. Such mechanisms are especially vital for these species during the dry season as salinity increases dramatically.…”
Section: Discussionmentioning
confidence: 99%
“…5). It has been reported that leaf nitrogen is involved in major alterations in carbon metabolism, including alterations in starch and sucrose contents in leaves (Hofstra et al, 1985;Dulormne et al, 2010) and the synthesis of organic acids to provide carbon skeletons for amino acid synthesis and to act as counter anions and prevent alkalinization (Scheible et al, 1997). Number of laboratory and greenhouse studies have shown that salinity reduces nitrogen accumulation in plants (Al-Rawahy et al, 1992).…”
Section: Discussionmentioning
confidence: 99%